mTOR Regulation of Glycolytic Metabolism in T Cells - Salmond, Robert J. (Frontiers in Cell and Developmental Biology, 2018)
T cell activation, differentiation and effector function is intrinsically linked to the regulation of metabolic pathways. Evidence has shown that inflammatory T cell responses are dependent upon the adoption of aerobic glycolytic metabolism. Furthermore, activation and regulation of the mechanistic target of rapamycin signaling pathway serves as a key determinant of T cell metabolism, with subsequent effects on T cell effector responses. In this mini-review, we discuss the mechanisms underpinning the function of the Warburg effect in T cell responses, and the role of mTOR in these processes.